Ризик-менеджмент як системоутворюючий елемент управління економічною безпекою підприємства [Електронний ресурс] - Дуднєва, Юлія Ернстівна; Dudnieva, Iu. E.; Артем’єв, Олександр Олександрович; Artemiev, О. О. (Одеса : Видавничий дім "Гельветика", 2025)
У статті досліджено роль ризик-менеджменту в системі управління економічною безпекою підприємства в умовах зростання невизначеності та дестабілізації економічного середовища. Обґрунтовано доцільність розгляду ризик-менеджменту не як допоміжної управлінської функції, а як системоутворюючого елементу корпоративного управління, що забезпечує узгодження стратегічних цілей, управлінських рішень і результатів діяльності підприємства. Показано, що економічна безпека формується як інтегральний результат функціонування управлінської системи, у межах якої ризик-менеджмент виконує інтеграційну, інформаційно-аналітичну та координаційну роль. Узагальнено функції та інструменти ризик-менеджменту, визначено їх вплив на підвищення стійкості, адаптивності та безперервності діяльності підприємства в умовах зростання ризиків і кризових трансформацій.

The article examines the role of risk management in the enterprise economic security management system under conditions of increasing uncertainty, environmental turbulence, and destabilizing economic factors. The relevance of the study is determined by the growing complexity of the external and internal environment of enterprises, intensified by global and local crises, structural economic shifts, and disruptions of production and logistics chains. Under such conditions, traditional reactive approaches to economic security management become insufficient, which necessitates the integration of proactive, risk-oriented management mechanisms into corporate governance systems. The study substantiates the feasibility of considering risk management not as a supplementary or isolated managerial function, but as a system-forming element of enterprise economic security management. This approach allows linking strategic objectives, managerial decision-making processes, and performance outcomes into a coherent management system. Economic security is interpreted not as an independent object of control, but as an integrated result of effective corporate governance, where risk management performs an integrative, analytical, and coordinating role. The article demonstrates that risk management ensures the transformation of uncertainty factors into structured and manageable risk parameters, enabling informed managerial decisions that account for both expected economic outcomes and potential adverse impacts on enterprise stability. The functions and instruments of risk management are systematized, and their influence on enterprise economic security is analyzed. It is shown that the implementation of a risk-oriented approach contributes to improving management coherence at strategic, tactical, and operational levels, enhancing enterprise resilience, adaptability, and continuity of operations. The obtained results create a foundation for further research aimed at developing applied models for assessing the effectiveness of risk management within enterprise economic security systems and can be used in corporate governance practice.
Risk management as a system-forming element in enterprise economic security management [Electronic resource]
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; ризик-менеджмент; економічна безпека підприємства; корпоративне управління; невизначеність; управлінські рішення; стійкість підприємства; risk management; economic security of an enterprise; corporate governance; uncertainty; management decisions; enterprise stability